2010
DOI: 10.1111/j.1469-7610.2010.02311.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of reading development and impairment from ages 3 to 8 years in Chinese children

Abstract: Findings suggest that the combination of phonological awareness, rapid naming and morphological awareness are essential in the early prediction of later reading difficulties in Chinese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 37 publications
7
128
0
4
Order By: Relevance
“…Specifically, the Spanish respondents agree more with the first criterion than do their U.S. counterparts, and they are less in agreement with the second criterion than are the Americans. This may be a reflection in practice of what research results have shown, that the value of oral language and of phonological processing is different in more consistent languages, such as Spanish, from their value in less consistent languages such as English [37][38][39][40][41][42]. In more consistent languages, phonological processing is more important than orthographic processing, while in less consistent languages, orthographic processing is more important [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the Spanish respondents agree more with the first criterion than do their U.S. counterparts, and they are less in agreement with the second criterion than are the Americans. This may be a reflection in practice of what research results have shown, that the value of oral language and of phonological processing is different in more consistent languages, such as Spanish, from their value in less consistent languages such as English [37][38][39][40][41][42]. In more consistent languages, phonological processing is more important than orthographic processing, while in less consistent languages, orthographic processing is more important [38].…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that these results must be interpreted with caution, given that the survey does not consider or specify the importance of language characteristics in explaining RD, as is established in some studies. Namely, the predictive value of phonological processing has been shown to differ according to the consistency of the language in question, being greater in more consistent languages than in less consistent ones [37][38][39][40][41][42].…”
mentioning
confidence: 99%
“…By contrast, there is no consensus on the influence of nonalphanumeric naming: some studies find no relationship to reading measures, while others do [21,24,25,40,41,44,48,49]. Consensus is also lacking as to what measure of reading is influenced by rapid naming, at what age, and with what type of language.…”
Section: Rapid Automatic Namingmentioning
confidence: 92%
“…The deficits which best distinguish dyslexic from nondyslexic children at age 7 were morphological awareness, rapid automatized naming, and word reading at age 5, suggesting that rapid automatized naming and morphological awareness are relatively strong correlates of developmental dyslexia in Chinese. Lei et al (2011) reported a 10-year longitudinal study in Beijing which revealed the dynamic change of reading disabled children and their heterogeneous characteristics in development. 261 children were followed from 3 to 8 years old.…”
Section: Early Prediction Of Reading Acquisition and Impairmentmentioning
confidence: 99%
“…However, recent studies have suggested RAN to be a consistent predictor of Chinese reading development, in which linking printed information with a given phonological representation arbitrarily is important. It predicts reading fluency and accuracy in both typically developing children and dyslexics (Ho & Lai, 1999;Ho et al, 2000;Shu, McBride-Chang, Wu, & Liu, 2006;Lei, Pan, Liu, McBride-Chang, Li, Zhang, Chen, Tardif, Liang, Zhang, & Shu, 2011; in press).…”
Section: Properties Of the Chinese Language And The Cognitive Correlamentioning
confidence: 99%